A Novel Antiviral Therapeutic Platform: Anchoring IFN-β to the Surface of Infectious Virions Equips Interferon-Evasive Virions with Potent Antiviral Activity - Hoda H. Jabbour; Alexander G. Bastian; Kayla B. DeOca; Mark D. Mannie (Viruses)
The COVID-19 pandemic highlighted the need for new therapeutic strategies to counter emerging pathogenic viruses. Herein, we introduce a novel fusion protein platform that enables antiviral targeting of distinct viral species based on host receptor specificity. Proof-of-concept studies focused on the human coronavirus NL63, which shares specificity for the ACE2 host receptor with the pandemic SARS-CoV and SARS-CoV-2 species. This antiviral fusion protein combines IFN-β with the soluble extracellular domain of ACE2 (IFNβ-ACE2). Both domains retained predicted bioactivities in that the IFN-β domain exhibited potent antiproliferative activity and the ACE2 domain exhibited full binding to the transmembrane SARS-CoV-2 Spike protein. In virus-washed (virus-targeted) and non-washed in vitro infection systems, we showed that the pool of IFNβ-ACE2 targeted to the virion surface had superior antiviral activity against NL63 compared to soluble ACE2, IFN-β, or the unlinked combination of ACE2 and IFN-β. The pool of IFNβ-ACE2 on the virion surface exhibited robust antiviral efficacy based on the preemptive targeting of antiviral IFN-β activity to the proximal site of viral infection. In conclusion, virus-targeted IFN-β places interferon optimally and antecedent to viral infection to constitute a new antiviral strategy.